Charge‐Transfer Complex Formation in Gelation: The Role of Solvent Molecules with Different Electron‐Donating Capacities. Issue 19 (27th March 2014) - Basak, Shibaji; Bhattacharya, Sumantra; Datta, Ayan; Banerjee, Arindam
Abstract A naphthalenediimide (NDI)‐based synthetic peptide molecule forms gels in a particular solvent mixture (chloroform/aromatic hydrocarbon, 4:1) through charge‐transfer (CT) complex formation; this is evident from the corresponding absorbance and fluorescence spectra at room temperature. Various aromatic hydrocarbon based solvents, including benzene, toluene, xylene (ortho, meta and para) and mesitylene, have been used for the formation of the CT complex. The role of different solvent molecules with varying electron‐donation capacities in the formation of CT complexes has been established through spectroscopic and computational studies.